Dark matter halo properties versus local density and cosmic web location. Issue 2 (23rd November 2018) - Goh, Tze; Primack, Joel; Lee, Christoph T; Aragon-Calvo, Miguel; Hellinger, Doug; Behroozi, Peter; Rodriguez-Puebla, Aldo; Eckholm, Elliot; Johnston, Kathryn
ABSTRACT: We study the effects of the local environmental density and the cosmic web environment (filaments, walls, and voids) on key properties of dark matter haloes using the Bolshoi–Planck Λ cold dark matter cosmological simulation. The z = 0 simulation is analysed into filaments, walls, and voids using the SpineWeb method and also the vide package of tools, both of which use the watershed transform. The key halo properties that we study are the specific mass accretion rate, spin parameter, concentration, prolateness, scale factor of the last major merger, and scale factor when the halo had half of its z = 0 mass. For all these properties, we find that there is no discernible difference between the halo properties in filaments, walls, or voids when compared at the same environmental density. As a result, we conclude that environmental density is the core attribute that affects these properties. This conclusion is in line with recent findings that properties of galaxies in redshift surveys are independent of their cosmic web environment at the same environmental density at z ∼ 0. We also find that the local web environment around galaxies of Milky Way's and Andromeda's masses that are near the centre of a cosmic wall does not appear to have any effect on the properties of those galaxies' dark matter haloes except on their orientation, although we find that it is rather rare to have such massive haloes near the centre of a relatively small cosmic wall.